KOHESI DAN KOHERENSI WACANA MOTIVASI “MARIO TEGUH GOLDEN WAYS” TENTANG WANITA PADA STASIUN METRO TV - Suryantini Putri, Ida Ayu (Humanis, 2014)
This study aims in order to analyze and comprehend the cohesion and coherence which is found in the discourse of motivation “Mario Teguh Golden Ways”. The episode of the discourse of motivation “Mario Teguh Golden Ways” that is used as the data in this study are “Emosi Wanita”, “Wanitaku Penghebatku” and “Wanita itu Maunya Apa”. The data is analyzed using theory of cohesion proposed by Halliday and Hasan and also use the theory of coherence proposed by Harimurti Kridalaksana. Through thesetheories, that can be found the grammatical cohesion, lexical cohesion and also coherency. Grammatical cohesions found from the data are reference, substitution, ellipsis and conjunction. Meanwhile, the lexical cohesions found from the data are repetition, antonym, synonym and collocation. Besides, in these three episodes, that is also found coherence, which are the additive temporal relationships, that is an additional relationship which relates to time, the relation of the conclusion background, relation of requirement results, comparison relation, implicative relation or description, result-reason relation and result-purpose relation.
Keywords: discourse, cohesion, coherence